Negative temperature coefficient thermal sensitive ceramic material with perovskite structure and preparation method thereof

By using a specific ratio of oxide raw materials, the coercion structure negative temperature coefficient thermal ceramics material is used to solve the problem of narrowing the temperature zone of the perovskite ore material, and the good linear relationship and negative temperature in the range of 473K to 1473K are realized The coefficient characteristics have widen the field of application and reduced the cost of use.

CN119350015APending Publication Date: 2025-01-24XINJIANG TECH INST OF PHYSICS & CHEM CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411445548.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The temperature zone of perovskite structural materials is narrow, which limits their application in the NTC field and makes it difficult to broaden their application temperature zone.

Method used

Using lanthanum trioxide, aluminum trioxide, ceria and calcium carbonate as raw materials, through processes such as mixing and grinding, calcination, cold isostatic pressing, high-temperature sintering and coating-sintered electrodes, a product with high performance in the range of 473K to 1473K is prepared. Perovskite structure negative temperature coefficient thermosensitive ceramic material with good linear relationship.

Benefits of technology

The application temperature area of ​​the perovskite material has been widened, so that it has obvious negative temperature coefficient characteristics in the range of 473K to 1473K, which is suitable for manufacturing NTC thermist resistance components. The problem of sensors reduces the actual cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350015A_ABST
    Figure CN119350015A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to a perovskite structure negative temperature coefficient thermal sensitive ceramic material and a preparation method thereof. The thermal sensitive ceramic material comprises the following components in percentage by weight: 71.36%-71.98% of lanthanum trioxide, 24.89%-25.1% of aluminum oxide, 1.05%-3.14% of cerium dioxide and 0.62%-1.86% of calcium carbonate, the chemical composition of the thermal sensitive ceramic material is La < 0.9 > CexCa < 0.1-x > AlO < 3 >, and x is equal to 0.025-0.075. The NTC thermistor has the advantages that the NTC thermistor has a good linear relation within the range of 473K-1473K, the resistance value and the B value are good in consistency, the resistance drift rate is as low as 2.18% after the NTC thermistor is aged for 500 hours at the high temperature, the stability is high, the service life is long, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, and in particular to a perovskite structure negative temperature coefficient thermistor ceramic material and a preparation method thereof. Background Art

[0002] NTC thermistor is a thermistor material with a negative temperature coefficient, and its resistance value decreases with the increase of temperature. This characteristic makes NTC thermistor play an important role in various electronic devices and is widely used in temperature measurement, temperature control, temperature compensation and other aspects. The manufacturing materials of NTC thermistor mainly include two or more metal oxides such as manganese, copper, silicon, cobalt, iron, nickel, zinc, etc., and semiconductor ceramics made by fully mixing, molding, sintering and other processes. NTC thermistor has a wide temperature range, including low-temperature type materials with a use temperature below 300℃, medium-temperature type thermistor materials with a use temperature of 300~500℃, and high-temperature type thermistor materials with a use temperature of 500~1000℃. This wide temperature adaptability enables NTC thermistor to play an important role in various environments and application conditions. In addition, the B value (temperature coefficient) of the NTC thermistor represents the sensitivity of the material to temperature changes. The larger the B value, the more sensitive the material is to temperature changes.

[0003] At present, the research on NTC materials involves various material systems, including spinel structure, perovskite structure and pyrochlore structure. Among them, spinel structure materials are mainly used for measuring temperature in low temperature zone, and perovskite structure materials are mainly used for measuring temperature in medium and high temperature zone. However, the temperature range of perovskite materials is relatively narrow, which seriously limits its application in the field of NTC. Therefore, it is necessary to broaden the NTC application temperature range of perovskite materials. LaAlO3 is a typical perovskite structure material, which has attracted widespread attention from researchers due to its high melting point, wide bandgap and excellent high temperature stability. Therefore, this paper takes LaAlO3 as the matrix material and develops a new type of perovskite structure negative temperature coefficient thermistor ceramic material with good linear relationship in the range of 473K~1473K. Summary of the invention

[0004] The present invention aims to provide a perovskite structure negative temperature coefficient thermistor ceramic material and a preparation method thereof. The material is made of lanthanum trioxide, aluminum trioxide, cerium dioxide and calcium carbonate as raw materials, and is subjected to mixed grinding, calcination, cold isostatic pressing, high temperature sintering, and electrode coating to obtain a material constant B 873K / 1473K = A new type of perovskite structure negative temperature coefficient thermistor ceramic material with a temperature range of 15565.34-18826.16 K. The resistance material has stable performance and good consistency. It has obvious negative temperature coefficient characteristics in the temperature range of 473K to 1473K and is suitable for manufacturing NTC thermistor components.

[0005] To achieve the above object, the present invention provides a wide temperature range perovskite structure negative temperature coefficient thermistor ceramic material, the thermosensitive ceramic material comprises by weight: lanthanum trioxide 71.36-71.98%, aluminum trioxide 24.89-25.1%, cerium dioxide 1.05-3.14% and calcium carbonate 0.62-1.86%, and its chemical composition is La 0.9 Ce x Ca 0.1- x AlO3, wherein x=0.025-0.075, preferably, x=0.025, 0.05, 0.075.

[0006] Preferably, the thermosensitive ceramic material constant is B 873K / 1473K =15565.34-18826.16K.

[0007] Another aspect of the present invention provides a method for preparing a wide temperature range perovskite structure negative temperature coefficient thermistor ceramic material, comprising the following steps:

[0008] a. Weigh lanthanum trioxide, aluminum trioxide, cerium dioxide and calcium carbonate and mix them to obtain a mixture powder;

[0009] b. Calcine and grind the mixture powder in step a to obtain La 0.9 Ce x Ca 0.1-x AlO3 powder;

[0010] c. Resuspend the La obtained in step b 0.9 Ce x Ca 0.1-x The AlO3 powder is pressed into blocks, the formed blocks are cold isostatically pressed, and then sintered to obtain a thermosensitive ceramic material;

[0011] d. Coating the thermistor ceramic material obtained in step c with an electrode, and then annealing to obtain a wide temperature range negative temperature coefficient thermistor ceramic material having a negative temperature coefficient characteristic in the temperature range of 473K to 1473K.

[0012] Preferably, in step a, the mixture is ground for 6-10 hours to obtain a mixture powder.

[0013] Preferably, in step b, the calcination temperature is 1200-1300° C., the calcination time is 10-20 hours, and the grinding time is 6-8 hours.

[0014] Preferably, in step c, the pressure for briquetting is 10-20 Kg / cm 2The briquetting time is 0.8-1.5min, cold isostatic pressing is carried out, the pressure is maintained at 250-350MPa for 3-5min, the sintering temperature is 1500-1600℃, and the sintering time is 15-20 hours.

[0015] Preferably, in step d, platinum paste electrodes are coated on both sides, and then annealed at a temperature of 800-900° C. for 30-60 minutes.

[0016] Specifically, the new type of wide temperature range negative temperature coefficient thermistor ceramic material described in the present invention is composed of lanthanum trioxide 71.36-71.98%, aluminum trioxide 24.89-25.1%, cerium dioxide 1.05-3.14% and calcium carbonate 0.62-1.86% by weight. Its chemical composition is La 0.9 Ce x Ca 0.1-x AlO3, where x = 0.025, 0.05, 0.075; the resulting material constant is B 873K / 1473K =15565.34-18826.16K, the specific operation is as follows:

[0017] a. Weigh 71.36-71.98% of lanthanum trioxide, 24.89-25.1% of aluminum trioxide, 1.05-3.14% of cerium dioxide and 0.62-1.86% of calcium carbonate respectively by weight, mix them, and grind the mixture in an agate mortar for 6-10 hours to obtain a powder;

[0018] b. The powder ground in step a was calcined at 1300°C for 10 hours and then ground for 6 hours to obtain La 1- x Ce x Al 1-y Nb y O3 powder;

[0019] c. The powder material obtained in step b is heated to 10-20 kg / cm 2 The block material is pressed into a block under a pressure of 0.8-1.5 min, and the formed block material is cold isostatically pressed at a pressure of 250-350 MPa for 3 min, and then sintered at a temperature of 1550°C for 15 hours to obtain a wide temperature range thermistor ceramic material;

[0020] d. Coat the ceramic material sintered in step c with platinum paste electrodes on both sides, and then anneal at 900°C for 30 minutes to obtain a material with a negative temperature coefficient characteristic in the temperature range of 25°C-1500°C, and the material constant is B 873K / 1473K = A new type of perovskite structure negative temperature coefficient thermistor ceramic material with a temperature range of 15565.34-18826.16K.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention has successfully developed a new type of perovskite structure negative temperature coefficient thermistor ceramic material, which has a good linear relationship in a wide temperature range of 473K to 1473K, effectively broadening the application field of the material system. The material system can cope with different external temperature environments, reducing the problem of forced replacement of sensors due to limited temperature zones during actual use, and reducing the actual use cost. In addition, the material system does not use chemical raw materials such as heavy metals, and the formula is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD diagram of the present invention shows that the diffraction peaks of all samples after doping with cerium dioxide and calcium carbonate can well match the perovskite structure of LaAlO3, and no second phase is generated, indicating that cerium and calcium are successfully doped into the LaAlO3 phase.

[0024] Figure 2 The sample La is co-doped with cerium dioxide and calcium carbonate. 0.9 Ce x Ca 0.1-x The temperature-resistance relationship diagram of AlO3 shows that after sintering, La 0.9 Ce x Ca 0.1-x The relationship between the logarithm of the resistivity (ρ) of AlO3 ceramics, lnρ, and the inverse of temperature 1000 / T. From the figure, it can be seen that in a certain temperature range, the resistivity of all samples decreases exponentially with the increase of temperature, and has a negative temperature coefficient behavior. However, the material constant B value and the resistivity value at 1000℃ of LaAlO3 material are large and difficult to be used in the NTC field. When doped with cerium and calcium, La 0.9 Ce x Ca 0.1-x AlO3 ceramic materials have NTC characteristics in the temperature range of 473K to 773K. 0.9 Ce x Ca 0.1-x In the temperature range of 473K to 1473K, lnρ of AlO3 material decreases with the increase of 1000 / T, showing negative temperature coefficient behavior and greatly reducing the material constant B value, making La 0.9 Ce x Ca 0.1-x AlO3 material has become a negative temperature coefficient thermistor ceramic material that can be used for temperature measurement in medium and high temperature ranges, and is expected to be used for temperature measurement in high temperature environments such as aviation and automobiles. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0026] The specific preparation method of the perovskite structure negative temperature coefficient thermistor ceramic material of the present invention is: S1, weighing materials; S2, mixing; S3, grinding; S4, pre-sintering; S5, secondary grinding; S6, tableting; S7, isostatic pressing; S8, sintering; S9, coating platinum slurry; S10, annealing; S11, welding leads.

[0027] Example 1

[0028] A method for preparing a wide temperature range perovskite structure negative temperature coefficient thermistor ceramic material, comprising the following steps:

[0029] a. According to La 0.9 Ce 0.075 Ca 0.025 The stoichiometric ratio of AlO3 is 71.36% of lanthanum trioxide, 24.89% of aluminum trioxide, 3.14% of cerium dioxide, and 0.615% of calcium carbonate, respectively, and the mixture is ground in an agate mortar for 6 hours to obtain a powder;

[0030] b. The powder ground in step a was calcined at 1300°C for 10 hours and then ground for 6 hours to obtain La 0.95 Ce 0.05 Al 0.975 Nb 0.025 O3 powder;

[0031] c. The powder material obtained in step b was heated to 10 kg / cm 2 The block material was pressed into a block under a pressure of 0.8 min, and the block material was cold isostatically pressed at a pressure of 250 MPa for 3 min, and then sintered at a temperature of 1550°C for 15 hours to obtain a high-temperature thermistor ceramic material.

[0032] d. Coat the ceramic material sintered in step c with platinum paste electrodes on both sides, and then anneal at 900°C for 30 minutes to obtain a material with a negative temperature coefficient characteristic in the temperature range of 473K to 1473K, with a material constant of B. 873K / 1473K = A new type of perovskite negative temperature coefficient thermistor ceramic material with a temperature of 11815.51K.

[0033] Example 2

[0034] A method for preparing a wide temperature range perovskite structure negative temperature coefficient thermistor ceramic material, comprising the following steps:

[0035] a. According to La 0.9 Ce 0.05 Ca 0.05The stoichiometric ratio of AlO3 is 71.67% of lanthanum trioxide, 24.99% of aluminum trioxide, 2.1% of cerium dioxide, and 1.235% of calcium carbonate, respectively, and the mixture is ground in an agate mortar for 8 hours to obtain a powder;

[0036] b. The powder ground in step a was calcined at 1300°C for 10 hours and then ground for 7 hours to obtain La 0.9 Ce 0.05 Ca 0.05 AlO3 powder;

[0037] c. The powder material obtained in step b was heated to 15 kg / cm 2 The block material was pressed into a block under a pressure of 1.5 min, and the block material was cold isostatically pressed at a pressure of 350 MPa for 3 min, and then sintered at a temperature of 1550°C for 15 hours to obtain a high-temperature thermistor ceramic material.

[0038] d. Coat the ceramic material sintered in step c with platinum paste electrodes on both sides, and then anneal at 900°C for 30 minutes to obtain a material with a negative temperature coefficient characteristic in the temperature range of 200°C-1300°C, with a material constant of B. 873K / 1473K = A new type of perovskite negative temperature coefficient thermistor ceramic material with a temperature of 13170.78K.

[0039] Example 3

[0040] A method for preparing a wide temperature range perovskite structure negative temperature coefficient thermistor ceramic material, comprising the following steps:

[0041] a. According to La 0.9 Ce 0.025 Ca 0.075 The stoichiometric ratio of AlO3 is 71.98% of lanthanum trioxide, 25.1% of aluminum trioxide, 1.05% of cerium dioxide, and 1.86% of calcium carbonate, respectively, and the mixture is ground in an agate mortar for 10 hours to obtain a powder;

[0042] b. The powder ground in step a was calcined at 1200°C for 15 hours and then ground for 6 hours to obtain La 0.9 Ce 0.025 Ca 0.075 AlO3 powder;

[0043] c. The powder material obtained in step b was heated to 15 kg / cm 2 The block material was pressed into a block at a pressure of 1.0 min, and the block material was cold isostatically pressed at a pressure of 350 MPa for 3 min, and then sintered at a temperature of 1600°C for 15 hours to obtain a high-temperature thermistor ceramic material.

[0044] d. Coat the ceramic material sintered in step c with platinum paste electrodes on both sides, and then anneal at 900°C for 30 minutes to obtain a negative temperature coefficient characteristic in the temperature range of 473K to 1473K. 873K / 1473K = A new type of perovskite negative temperature coefficient thermistor ceramic material with a temperature of 11665.34K.

[0045] Example 4 (Comparative Example)

[0046] a. According to the stoichiometric ratio of LaAlO3, 15.222 parts of lanthanum trioxide and 4.778 parts of aluminum trioxide were weighed and mixed, and the mixed raw materials were placed in an agate mortar and ground for 8 hours to obtain a powder;

[0047] b. calcining the powder ground in step a at 1300° C. for 10 hours and grinding for 6 hours to obtain LaAlO3 powder;

[0048] c. The powder material obtained in step b was heated to 20 kg / cm 2 The block material was pressed into a block under a pressure of 2 minutes, and the formed block material was cold isostatically pressed at a pressure of 300 MPa for 3 minutes, and then sintered at a temperature of 1575°C for 20 hours to obtain a perovskite-type medium- and high-temperature thermal-sensitive ceramic material;

[0049] d. Coat the front and back sides of the thermistor ceramic material sintered in step c with platinum paste electrodes, and then anneal at 900°C for 30 minutes to obtain a negative temperature coefficient characteristic in the temperature range of 873K to 1473K, and the material constant is B 873K / 1473K =18826.16K perovskite high temperature thermistor ceramic resistor material.

[0050] Example 5

[0051] Compare any of the novel perovskite negative temperature coefficient thermistor ceramic materials obtained in Examples 1-4 with Example 5, see Figure 1 The results show that with the increase of cerium dioxide and calcium carbonate content, the diffraction peaks of all samples can well match the perovskite structure of LaAlO3, and no second phase is generated, indicating that cerium dioxide and calcium carbonate are successfully doped into the LaAlO3 phase.

[0052] Figure 2 The sample La is obtained by Ce-Ca co-doping 0.9 Ce x Ca 0.1-x The temperature resistance diagram of AlO3, Figure 2 The left picture shows the La after sintering of Example 1-3. 0.9 Ce x Ca 0.1-xThe relationship between the resistance and temperature T of AlO3 ceramics, Figure 2 The right picture shows the La after sintering of Example 1-3. 0.9 Ce x Ca 0.1-x The relationship between the logarithm of the resistivity (ρ) of AlO3 ceramics, lnρ, and the inverse of temperature 1000 / T, in which LAO is LaAlO3, CC1 is Example 1, CC2 is Example 2, and CC3 is Example 3. It can be seen from the figure that the resistivity of all samples decreases exponentially with increasing temperature within a certain temperature range, and has a negative temperature coefficient behavior. However, the material constant B value and the resistivity value at 1000°C of LaAlO3 material are large and difficult to be used in the NTC field. When doped with cerium and calcium, LaAlO3 is obviously 0.9 Ce x Ca 0.1-x AlO3 ceramic materials have NTC characteristics in the temperature range of 473K to 773K. 0.9 Ce x Ca 0.1-x In the temperature range of 473K to 1473K, lnρ of AlO3 material decreases with the increase of 1000 / T, showing negative temperature coefficient behavior and greatly reducing the material constant B value, making La 0.9 Ce x Ca 0.1-x AlO3 material has become a negative temperature coefficient thermistor ceramic material that can be used for temperature measurement in medium and high temperature ranges, and is expected to be used for temperature measurement in high temperature environments such as aviation and automobiles.

[0053] The NTC thermistor of the present invention has a good linear relationship within the range of 473K to 1473K, has good consistency between resistance value and B value, has a resistance drift rate as low as 2.18% after aging for 500 hours at high temperature, has the advantages of high stability, long service life, etc.; in addition, the powder particles prepared by the present invention have high dispersion, are not prone to agglomeration, and have high chip strength.

[0054] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.

[0055] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.

Claims

1. A perovskite structure negative temperature coefficient thermistor ceramic material, characterized in that: The thermosensitive ceramic material comprises, by weight percentage, 71.36-71.98% of lanthanum trioxide, 24.89-25.1% of aluminum trioxide, 1.05-3.14% of cerium dioxide and 0.62-1.86% of calcium carbonate, and its chemical composition is La 0.9 Ce x Ca 0.1-x AlO3, wherein x = 0.025-0.

075.

2. The perovskite structure negative temperature coefficient thermistor ceramic material according to claim 1, characterized in that: The thermosensitive ceramic material constant is B 873K / 1473K℃ =15565.34-18826.16K.

3. A method for preparing the perovskite structure negative temperature coefficient thermistor ceramic material according to claim 1 or 2, the preparation method comprising the following steps: a. Weigh lanthanum trioxide, aluminum trioxide, cerium dioxide and calcium carbonate and mix them to obtain a mixture powder; b. Calcine and grind the mixture powder in step a to obtain La 0.9 Ce x Ca 0.1-x AlO 33 Powder; c. Resuspend the La obtained in step b 0.9 Ce x Ca 0.1-x The AlO3 powder is pressed into blocks, the formed blocks are cold isostatically pressed, and then sintered to obtain a thermosensitive ceramic material; d. Coating the thermistor ceramic material obtained in step c with an electrode, and then annealing to obtain a perovskite structured negative temperature coefficient thermistor ceramic material having a negative temperature coefficient characteristic in the temperature range of 473K to 1473K.

4. The preparation method according to claim 3, characterized in that: In step a, the mixture is ground for 6-10 hours after mixing to obtain a mixture powder.

5. The preparation method according to claim 3, characterized in that: In step b, the calcination temperature is 1200-1300° C., the calcination time is 10-20 hours, and the grinding time is 6-8 hours.

6. The preparation method according to claim 3, characterized in that: In step c, the pressure of the briquetting is 10-20Kg / cm 2 The briquetting time is 0.8-1.5min; cold isostatic pressing is performed, and the pressure is maintained at 250-350MPa for 3-5min; the sintering temperature is 1500-1600℃, and the sintering time is 15-20 hours.

7. The preparation method according to claim 3, characterized in that: In step d, platinum paste electrodes are coated on both sides, and then annealed at a temperature of 800-900° C. for 30-60 minutes.

Citation Information

Patent Citations

  • Metal oxide sintered bodies for thermistors, thermistor elements, thermistor temperature sensors, and methods for preparing metal oxide sintered bodies for thermistors

    CN102300829A

  • Low-B-value high-sensitivity thermistor material suitable for wide-temperature-range temperature measurement and preparation method of low-B-value high-sensitivity thermistor material

    CN116639976A

  • Thermal sensitive ceramic material with negative temperature coefficient in high-temperature region and preparation method of thermal sensitive ceramic material

    CN117819968A

  • Thermal sensitive ceramic material with negative temperature coefficient in medium-high temperature region and preparation method of thermal sensitive ceramic material

    CN117923898A

  • Thermistor

    EP0974983A1